The encyclopedia of farm animal nutrition - Fuller, M. F. (CABI Pub., 2004)
"The Encyclopedia of Farm Animal Nutrition covers the whole of nutrition, embracing a wide range of disciplines, including physiology, biochemistry, veterinary medicine and feed technology. It provides information on the nutrition of every type farm animal found in both developing and developed countries, including birds and fish. Contents include: basic aspects of digestion and metabolism; energy, protein, minerals and vitamins; feed intake; common feeds; feed processing; deficiency diseases and nutritional disorders." "The encyclopedia contains approximately 2000 entries, contributed by 95 international authors. Entries vary from short definitions to more discursive articles of up to 2000 words. Longer entries are supported by references to important original papers and review, and all entries are fully cross-referenced to related entries within the book." "It is a valuable source of information to anyone working in animal nutrition, and an essential acquisition for librarians in agricultural and veterinary science, worldwide."--Jacket